2014
DOI: 10.1063/1.4893977
|View full text |Cite
|
Sign up to set email alerts
|

Gated Si nanowires for large thermoelectric power factors

Abstract: We investigate the effect of electrostatic gating on the thermoelectric power factor of p-type Si nanowires (NWs) of up to 20nm in diameter in the [100], [110] and [111] crystallographic transport orientations. We use atomistic tight-binding simulations for the calculation of the NW electronic structure, coupled to linearized Boltzmann transport equation for the calculation of the thermoelectric coefficients. We show that gated NW structures can provide ~5x larger thermoelectric power factor compared to dop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…This is attributed to the adverse interdependence of the electrical conductivity and Seebeck coefficient via the carrier density, which proves very difficult to overcome. To achieve power factor improvements, current efforts revolve around engineering the density of states of lowdimensional materials, 2-6 modulation doping, [7][8][9][10] introducing energy resonances in the density of states, 11,12 and energy filtering in nanocomposites and superlattices. [13][14][15][16][17][18][19][20][21][22] Although theoretical works indicate that power factor improvements are possible, to-date experiments do not commonly demonstrate significant success in realizing these improvements.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the adverse interdependence of the electrical conductivity and Seebeck coefficient via the carrier density, which proves very difficult to overcome. To achieve power factor improvements, current efforts revolve around engineering the density of states of lowdimensional materials, 2-6 modulation doping, [7][8][9][10] introducing energy resonances in the density of states, 11,12 and energy filtering in nanocomposites and superlattices. [13][14][15][16][17][18][19][20][21][22] Although theoretical works indicate that power factor improvements are possible, to-date experiments do not commonly demonstrate significant success in realizing these improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Here Vsd is the bias voltage. There is some recent observation [22][23][24][25][26][27][28][29][30][31][32] which also reveals the same behaviour. T=0K T=3K T=5K T=0K T=3K T=5K T=0K T=3K 0 …”
Section: Discussion Of Resultsmentioning
confidence: 59%
“…Several recent studies suggested techniques to avoid transport in the presence of IIS have been proposed, such as modulation doping techniques [46,47], or gating the channel materials [48,49,50,51,52,53]. In this way, the high carrier densities can be achieved without the use of direct doping, and the phonon-limited performance would be…”
Section: K Q D mentioning
confidence: 99%
“…An important point we stressed in Ref. [49], is that SRS is not a strong degrading mechanism in channels with feature sizes >10nm, , despite the fact that the gate field tends to shift carriers on the surface. The reason is that the internal electric fields required to achieve charge accumulation are weak (compared to the fields required to achieve inversion layers, for example).…”
Section: K Q D mentioning
confidence: 99%